Effect of Diesel Compositions on the Performance of Lubricity Improver - PANG Bo, HUANG Zhan-kai (Cailiao Baohu, 2021)
With focusing on the different effects of diesel lubricity improver(also known as anti-wear agent)on different diesel oils, two batches of diesel oils from H refinery were chosen as samples, and the components of diesel oil were analyzed by gas chromatography-mass spectrometry and simulated distillation.Then, the effects of alkanes, cycloalkanes and aromatics on the performance of propylene glycol monooleate and glyceryl monooleate lubricity improvers were explored by measuring the wear scar diameter.Result showed that cycloparaffins had a negative effect on the performance of lubricity improver, while paraffins and aromatics had no direct effects.It was also assumed that cycloparaffins decreased the compactness of the lubricating film through spatial steric resistance, thus reducing the effect of lubricity improver.Finally, through adding ester-based lubricity improver with stronger hydrogen bonds, the interference effect of cycloparaffins could be reduced, and the lubricity of diesel oil could be improved.